The role of environmental knowledge, attitudes and initiatives in the development of a tourism product - Niezgoda, Agnieszka (Turyzm/Tourism, 2012)
The article looks at environmental activities undertaken by the various stakeholders engaged in the development of a tourism product. Special attention is given to the impact of tourists' behaviour on tourist destination products and on future ecology-related actions of service providers. The meaning of environmental awareness is explained as well as its relationship with the concepts of sustainable tourism and eco-tourism. Some problems arising from demand for eco-products are discussed.